Incidence of viral respiratory infections in a prospective cohort of outpatient and hospitalized children aged ≤5 years and its associated cost in Buenos Aires, Argentina. Issue 1 (December 2015) - Marcone, Débora; Durand, Lizette; Azziz-Baumgartner, Eduardo; Vidaurreta, Santiago; Ekstrom, Jorge; Carballal, Guadalupe; Echavarria, Marcela
Abstract Background Although information about the incidence of viral respiratory illnesses and their associated cost can help health officials explore the value of interventions, data are limited from middle-income countries. Methods During 2008–2010, we conducted a prospective cohort study and followed 1, 800 Argentinian children aged ≤5 years to identify those children who were hospitalized or who sought care at an emergency room with any acute respiratory infection sign or symptom (e.g., rhinorrhea, cough, wheezing, tachypnea, retractions, or cyanosis). Respiratory samples were obtained for respiratory syncytial virus, influenza, parainfluenza, adenovirus, and metapneumovirus testing by immunofluorescence and for rhinovirus by real-time reverse transcription polymerase chain reaction. Results The incidence of respiratory syncytial virus (24/1000 children-years), human metapneumovirus (8/1000 children-years), and influenza (8/1000 children-years) illnesses was highest among hospitalized children aged <6 months and decreased among older children. In contrast, the incidence of rhinovirus was highest (12/1000 children-years) among those aged 6–23 months. In the emergency room, the incidence of rhinovirus was 459; respiratory syncytial virus 352; influenza 185; parainfluenza 177; metapneumovirus 130; and adenovirus 73/1, 000 children-years. The total cost of hospitalization was a median of US529 (Interquartile range, US362–789). Conclusions Our findings indicate that respiratory viruses, in particular rhinovirus, respiratory syncytial virus, metapneumovirus, and influenza may be associated with severe illness causing substantial economic burden.